Volunteer trials of a novel improvised dry decontamination protocol for use during mass casualty incidents as part of the UK'S Initial Operational Response (IOR). - Richard Amlôt; Holly Carter; Lorna Riddle; Joanne Larner; Robert P Chilcott (PLoS ONE)
Previous studies have demonstrated that rapid evacuation, disrobing and emergency decontamination can enhance the ability of emergency services and acute hospitals to effectively manage chemically-contaminated casualties. The purpose of this human volunteer study was to further optimise such an "Initial Operational Response" by (1) identifying an appropriate method for performing improvised skin decontamination and (2) providing guidance for use by first responders and casualties. The study was performed using two readily available, absorbent materials (paper towels and incontinence pads). The decontamination effectiveness of the test materials was measured by quantifying the amount of a chemical warfare agent simulant (methyl salicylate) removed from each volunteer's forearm skin. Results from the first study demonstrated that simulant recovery was lower in all of the dry decontamination conditions when compared to matched controls, suggesting that dry decontamination serves to reduce chemical exposure. Blotting in combination with rubbing was the most effective form of decontamination. There was no difference in effectiveness between the two absorbent materials. In the following study, volunteers performed improvised dry decontamination, either with or without draft guidelines. Volunteers who received the guidance were able to carry out improvised dry decontamination more effectively, using more of the absorbent product (blue roll) to ensure that all areas of the body were decontaminated and avoiding cross-contamination of other body areas by working systematically from the head downwards. Collectively, these two studies suggest that absorbent products that are available on ambulances and in acute healthcare settings may have generic applicability for improvised dry decontamination. Wherever possible, emergency responders and healthcare workers should guide casualties through decontamination steps; in the absence of explicit guidance and instructions, improvised dry decontamination may not be performed correctly or safely.